Assessing the effectiveness of gender quotas in enhancing women's political leadership - A case study of Zimbabwe, Kenya and South Africa - Hammond, Ama (University of Pretoria, 2022)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.